Main‐Chain Oligomers from NiII‐ and CuII‐Centered Unsymmetrical N2O2 Schiff‐Base Complexes: Synthesis and Spectral, Structural, and Second‐Order Nonlinear Optical Properties. Issue 29 (29th August 2014) - Celedón, Salvador; Dorcet, Vincent; Roisnel, Thierry; Singh, Anu; Ledoux‐Rak, Isabelle; Hamon, Jean‐René; Carrillo, David; Manzur, Carolina
Abstract: Oligomeric main‐chain Schiff‐base compounds4 and5 have been synthesized by the trans‐esterification of their respective doubly functionalized monomeric precursors [M(η 5 ‐C5 H5 )Fe(η 5 ‐C5 H4 )C(=O)CH=C(4‐C6 H4 OH)NCH2 CH2 N=CH‐(2‐O, 4‐CO2 H–C6 H3 )] [M = Ni (2 ), Cu (3 )] in dmf. The new compounds were characterized by elemental analysis, FTIR and multidimensional NMR spectroscopy, mass spectrometry, and cyclic voltammetry. Compounds2, 3, and6, the corresponding amide of2, were characterized by X‐ray structural investigation. Gel permeation chromatography established that oligomers4 and5 are formed of approximately six monomeric units, and differential scanning calorimetry and thermal gravimetric analysis indicated that they are thermally stable with decomposition temperatures exceeding 230 °C. Harmonic light scattering measurements showed that compounds2 –5 exhibit rather high second‐order nonlinear responses, between 224 × 10 –30 and 399 × 10 –30 esu, with hyperpolarizability β 1.91 values that increase significantly on passing from the monomeric to the oligomeric species. Abstract : The esterification of binuclear phenol and carboxylic acid functionalized ferrocenyl‐containing metal‐centered Schiff‐base complexes (M = Ni, Cu) in the presence of N, N′ ‐dicyclohexylcarbodiimide and dmap afforded their corresponding main‐chain oligomers. They are formed of approximately six monomeric units, are redox active, and exhibit good thermal stability and high second‐order NLO responses.